2019
DOI: 10.21432/cjlt27798
|View full text |Cite
|
Sign up to set email alerts
|

Le codesign d’une plateforme numérique fondé sur des principes au service de l’agentivité des enseignantes et des enseignants en contexte de développement professionnel | Co-Design of a Digital Platform Based on Principles Supporting Teachers’ Agency in the Context of Professional Development

Abstract: Les enseignantes et les enseignants du collégial partagent avec les établissements d’enseignement la responsabilité de leur développement professionnel. Cet article a trait au codesign d’une plateforme numérique au service de l’agentivité des enseignants en situation de développement professionnel. Le processus de codesign a inclus le repérage des freins au développement professionnel ainsi que l’identification des buts de niveau motivationnel. Les résultats mettent l’accent sur les buts fonctionnels et opérat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
1
0
2
Order By: Relevance
“…Recommender systems are guides that can help teachers find solutions to their documented needs in a context where teachers are responsible for their own professional development and showing agency, a concept we define below (Deschênes & Laferrière, 2019). Teachers have reported that they wish to receive recommendations for resources or people based on their preferences, goals and search topics or recommendations for resources other teachers found interesting and useful.…”
Section: Introductionmentioning
confidence: 99%
“…Recommender systems are guides that can help teachers find solutions to their documented needs in a context where teachers are responsible for their own professional development and showing agency, a concept we define below (Deschênes & Laferrière, 2019). Teachers have reported that they wish to receive recommendations for resources or people based on their preferences, goals and search topics or recommendations for resources other teachers found interesting and useful.…”
Section: Introductionmentioning
confidence: 99%
“…Le projet Écrits en chantier a bel et bien permis la création de matériel didactique disponible sur Internet et la mise sur pied de formations diverses (Lanctôt, 2017). Or, au collégial, les personnes enseignantes sont responsables de leur développement professionnel (Deschênes, 2021) et rien ne les oblige à s'intéresser à ces formations.…”
Section: Problématiqueunclassified
“…Ainsi, la problématique a permis de mettre en évidence qu'en dépit d'une littérature abondante sur le DP, le contexte du niveau collégial soulève encore certains questionnements et qu'il demeure un sujet d'intérêt (Deschênes, 2021). Cela nous suggère de réfléchir aux conditions nécessaires pour favoriser un DP de qualité.…”
Section: Satisfaction Des Besoins Fondamentaux Et Liens Avec Les Diff...unclassified